Diagnostic Utility of Claudin-4 Immunohistochemistry in Distinguishing Adenocarcinoma Cells from Reactive Mesothelial Cells in Effusion Cytology - Ginnavaram, Mihira; Pamu, Pramod Kumar; Kesarapu, Swetha; Ramakrishna, Narayanan (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Differentiating adenocarcinoma cells from reactive mesothelial cells in cases of effusion remains a diagnostic challenge due to overlapping morphological features. Claudin-4, a tight junction protein expressed in epithelial but absent in mesothelial cells, has emerged as a potential immunohistochemical (IHC) marker for this distinguishing between these cell types.Objective: to evaluate the diagnostic utility of Claudin-4 immunohistochemistry in differentiating adenocarcinoma cells from reactive mesothelial cells in effusion cytology.Methods: This prospective study was conducted at the Department of Pathology, Nizam’s Institute of Medical Sciences, Hyderabad, India, between June 2023 and December 2024. A total of 77 formalin-fixed paraffin-embedded cell block samples from effusion fluids (pleural, ascitic, and peritoneal) were analyzed. Inclusion criteria comprised cases diagnosed as malignant or reactive on cytology. Claudin-4 immunostaining was performed by using EP417 clone. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of Claudine for differentiating malignant versus non-malignant effusion was calculated.Results: Out of the 77 studied cases, 57 were malignant and 20 were non-malignant. Claudin-4 showed positive membranous staining in 50/57 malignant cases (87.72%) and in none of the non-malignant cases (100% specificity). The PPV was 100%, and NPV was 74.10%. Pulmonary adenocarcinoma was the most common malignancy showing Claudin-4 positivity. Claudin demonstrated excellent specificity for diagnosis of malignant effusions. Conclusion: Claudin-4 immunohistochemistry is highly specific as a reliable marker for differentiating malignant cells from reactive mesothelial cells. Its high specificity and positive predictive value make it a valuable diagnostic tool. However, a negative Claudin-4 immunohistochemistry results should be interpreted cautiously, particularly in clinically suspicious cases.